Life history and chemical ecology of the Warrior wasp Synoeca septentrionalis (Hymenoptera: Vespidae, Epiponini) - Santos, Eliaber B. (PLoS One, 2018)
Swarm-founding ‘Warrior wasps’ (Synoeca spp.) are found throughout the tropical regions of South America, are much feared due to their aggressive nest defence and painful sting. There are only five species of Synoeca, all construct distinctive nests that consist of a single sessile comb built onto the surface of a tree or rock face, which is covered by a ribbed envelope. Although locally common, research into this group is just starting. We studied eight colonies of Synoeca septentrionalis, a species recently been described from Brazil. A new colony is established by a swarm of 52 to 140 adults that constructs a colony containing around 200 brood cells. The largest colony collected containing 865 adults and over 1400 cells. The number of queen’s present among the eight colonies varied between 3 and 58 and no clear association between colony development and queen number was detected. Workers and queens were morphologically indistinguishably, but differences in their cuticular hydrocarbons were detected, particularly in their (Z)-9-alkenes. The simple cuticular profile, multiple queens, large size and small number of species makes the ‘Warrior wasps’ an excellent model group for further chemical ecology studies of swarm-founding wasps.